Magnetic poly(β-cyclodextrin) combined with solubilizing agents for the rapid bioaccessibility measurement of polycyclic aromatic hydrocarbons in soils. (15th December 2021) - Qin, Shibin; Qi, Shihua; Li, Xiaoshui; Shi, Qiuyun; Li, Huan; Mou, Xiaoxuan; Zhang, Yuan
Abstract: The rapid determination of the bioaccessibility of polycyclic aromatic hydrocarbons (PAHs) in soils is challenging due to their slow desorption rates and the insufficient extraction efficiency of the available methods. Herein, magnetic poly(β-cyclodextrin) microparticles (Fe3 O4 @PCD) were combined with hydroxypropyl-β-cyclodextrin (HPCD) or methanol (MeOH) as solubilizing agents to develop a rapid and effective method for the bioaccessibility measurement of PAHs. Fe3 O4 @PCD was first validated for the rapid and quantitative adsorption of PAHs from MeOH and HPCD solutions. The solubilizing agents were then coupled with Fe3 O4 @PCD to extract PAHs from soil-water slurries, affording higher extractable fractions than the corresponding solution extraction and comparable to or higher than single Fe3 O4 @PCD or Tenax extraction. The desorption rates of labile PAHs could be markedly accelerated in this process, which were 1.3–12.0 times faster than those of single Fe3 O4 @PCD extraction. Moreover, a low HPCD concentration was sufficient to achieve a strong acceleration of the desorption rate without excessive extraction of the slow desorption fraction. Finally, a comparison with a bioaccumulation assay revealed that the combination of Fe3 O4 @PCD with HPCD could accurately predict the PAH concentration accumulated in earthworms in three field soil samples, indicating that the method is a time-saving and efficient procedure to measure the bioaccessibility of PAHs. Graphical abstract: Image 1 Highlights: Solubilizing agents promoted the adsorption of PAHs on magnetic poly(β-cyclodextrin). Magnetic particle was first coupled with solubilizer to measure PAH bioaccessibility. The present method markedly accelerated the desorption rate of labile PAHs from soil. Low dosage of the solubilizing agent was sufficient to greatly speed up the rate. A 12 h extraction exhibited highly linear correlation with the bioaccumulation assay.